Teacher Efforts In Increase Participation Study Student Through Learning Models Cooperative Type Think–Pair–Share (TPS) in Fiqh Subject at MTSN 1 Bima - Awalul Khair; Khairudin; Nurdinawati (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to determine the application of the Think-Pair-Share (TPS) cooperative learning model in increasing student learning participation in Fiqh subjects at MTsN 1 Bima. This study uses a qualitative approach with a descriptive type. The subjects of the study were 30 eighth-grade students. Data collection techniques were carried out through observation, interviews, and documentation, while data validity used triangulation of sources, techniques, and time. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study showed that student learning participation before the implementation of the TPS model was in the low category, namely 35%. After the implementation of the TPS model, student learning participation increased to 75% in the high category. This increase was seen from the increased activeness of students in asking questions, answering questions, discussing, and presenting discussion results in front of the class. Thus, it can be concluded that the application of the Think-Pair-Share (TPS) type cooperative learning model is effective in increasing student learning participation in the Fiqh subject at MTsN 1 Bima.